Diagnostics and treatment abdominal pain algorithm: expert council resolution - V. T. Ivashkin; I. V. Mayev; T. L. Lapina; M. F. Osipenko; M. A. Livzan; Yu. A. Kucheryavy; V. B. Grynevich; Ye. K. Baranskaya; O. M. Drapkina; A. A. Sheptulin; D. I. Abdulganiyeva; O. P. Alekseyeva; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.